Narrative inquiry in language teaching and learning research (Second language acquisition research series: theoretical and methodological issues, 2014)
"This text provides an entry-level introduction to narrative inquiry methods, grounded in empirical research within the fields of language teaching and learning. The book discusses basic concepts, explains how and why these methods have been used in language teaching and learning research, and outlines different approaches covered by this research. Narrative Inquiry in Language Teaching and Learning Research is a focused and practical guide for readers interested in understanding or carrying out narrative studies"--Provided by publisher.